2007
DOI: 10.1007/s10916-007-9060-5
|View full text |Cite
|
Sign up to set email alerts
|

A Norm Utilisation for Scarce Hospital Resources: Evidence from Operating Rooms in a Dutch University Hospital

Abstract: Background Utilisation of operating rooms is high on the agenda of hospital managers and researchers. Many efforts in the area of maximising the utilisation have been focussed on finding the holy grail of 100% utilisation. The utilisation that can be realised, however, depends on the patient mix and the willingness to accept the risk of working in overtime. Materials and methods This is a mathematical modelling study that investigates the association between the utilisation and the patient mix that is served a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…Wullink et al [120], for instance, examined whether it is preferred to reserve a dedicated operating room or to reserve some capacity in all elective operating rooms in order to improve the responsiveness to emergencies. Using discrete-event simulation they found that the responsiveness, the amount [71,72,112] of overtime and the overall operating room utilization significantly improved when the reserved capacity was spread over multiple operating rooms. Bowers and Mould [17] group orthopaedic urgencies into trauma sessions and use Monte-Carlo simulation to determine which session length balances the amount of session overruns with an acceptable utilization rate.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wullink et al [120], for instance, examined whether it is preferred to reserve a dedicated operating room or to reserve some capacity in all elective operating rooms in order to improve the responsiveness to emergencies. Using discrete-event simulation they found that the responsiveness, the amount [71,72,112] of overtime and the overall operating room utilization significantly improved when the reserved capacity was spread over multiple operating rooms. Bowers and Mould [17] group orthopaedic urgencies into trauma sessions and use Monte-Carlo simulation to determine which session length balances the amount of session overruns with an acceptable utilization rate.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Note that simulation is often preferred as the solution technique to study complex stochastic set- [3,5,6,9,10,17,20,25,26,27,28,41,43,44,49,54,60,62,63,64,70,75,76,78,79,82,83,84,86,88,92,94,97,104,109,110,111,112,113,114,115,120,122] other [20,35,37] tings, as it features an extensive modeling flexibility. Next to arrival and duration uncertainty, other types of uncertainty may be addressed.…”
Section: Uncertaintymentioning
confidence: 99%
“…Obviously, the more robust the program, the more time needs to be reserved, and thus the lower the OR utilization. Consequently, robustness and utilization should always be jointly considered as performance criteria (Van Houdenhoven et al 2007a).…”
Section: Robustnessmentioning
confidence: 99%
“…Capacity planning involves resource dimensioning and allocation within the constraints set by target production agreements, and agreements on utilization and availability of resources (Van Houdenhoven et al 2007a). It also involves reserving slack time for dealing with the inherent variability of the process.…”
Section: Capacity Planningmentioning
confidence: 99%
“…[8] Utilisation of 100% is referred to as 'the holy grail' , because it is essentially sustainably unattainable owing to unavoidable variations in procedures and loading. [9] This study investigated the efficiency of an operating theatre complex in a large private hospital in SA by measuring utilisation levels and using the result as a proxy for the effectiveness with which the complex can generate income for the hospital.…”
mentioning
confidence: 99%